A global framework for integrating public health into wellbeing: why a public wellbeing system is needed - László L. Lippai; László L. Lippai; Klára Tarkó; Klára Tarkó; Attila Tanyi; Attila Tanyi; Zsófia Kollányi; Zsófia Kollányi; Mária Arapovics; József Vitrai; József Vitrai (Frontiers in Public Health)
There is a growing focus on public health initiatives that prioritize wellbeing. The main question of our study is whether this, in its current form, can really represent a new response to the challenges of previous strategies, or whether there is a greater chance that it will essentially reproduce the problems associated with the paradoxical situation of public health. Based on a review, analysis and evaluation of the literature on wellbeing in public health, we outlined the foundations of a new meta-theory of wellbeing and a possibility for its social application. In our view, wellbeing is seen as a social representation of a combination of positive and negative freedom of choice concerning the quality of everyday life, used in a positioning process involving both individual and collective aspects. Health is a particular aspect of the social representation and positioning of wellbeing, which encompasses aspects of the physical, psychological, social and spiritual functioning of individuals. The wellbeing meta-theory also opens up the possibility for more effective solutions to the social challenges related to wellbeing and salutogenetic health. It underscores the importance of the need for a dedicated social subsystem where the goals and organizational culture of the organizations involved are focused on wellbeing and health promotion. In our study, we consider this to be the Public Wellbeing System (PWS). Our conclusion is that the development and operation of a new set of institutions—the Public Wellbeing System (PWS)—based on the co-production of services that meet the needs and demands of society, and dedicated to the promotion of wellbeing, may provide an opportunity to overcome the public health paradox.